Regulation status of quarantine pests of rice seeds in the Economic Community of West African States (ECOWAS) - Bachabi, F.; Gumedzoe, M.Y.D.; Maroya, N.G.; Ayenan, M.A.T.; Saidou, A.; Sere, Y. (2017)
The ever growing international trade has limited efforts towards the prevention of introduction, spread and establishment of invasive organisms. Non-native pests can cause severe loss of production and lead to restriction in exchange of genetic materials and seed marketing across regions. Regulating pests’ movement through quarantine measures and establishment of regional boards has been identified as a way to deal with introduction and expansion of invasive organisms. This review analyzes the different pest regulations in the West African sub-region with a specific focus on the implementation of quarantine measures in rice as a case study. The various regulations related to seed production, certification and marketing, and quarantine regulations in West Africa were analyzed and their enforcement and performance were assessed through comparison to international standards, especially the International Plant Protection Convention (IPPC). Although a regional regulation on seeds and phytosanitary measures has been elaborated, ECOWAS countries are still enforcing their national phytosanitary legislations, which are nearly the same in all West African countries - they all aim at ensuring plant health by applying preventive and curative measures to prevent the introduction and spread of pests in their territory by controlling the import and export of plant materials and disseminating appropriate pest management techniques to boost agricultural production. Most ECOWAS countries are yet to submit their phytosanitary legislation to IPPC to comply with Article VII.2i of the endorsed convention. In addition, the entry points are not well defined and provided to the IPPC according to the Article VII.2d of the convention. When the quarantine list is available, the organisms regulated for each crop species are not stated, posing a real problem not only for rice genetic resource exchanges for research purposes but also for rice seed trade. Efforts and resources should be devoted by each country to research on pests and regulatory mechanisms in order to define, among others, pest status in the region, and to update regularly the quarantine pests list in the West African region.